Relationship Between Family Support and Self Care Agency with the Quality of Living Type II Diabetes Patients - Ferawati; Kurniati, Mei Fitria (Institut Ilmu Kesehatan STRADA Indonesia, 2019)
Background: Diabetes Mellitus is a chronic disease characterized by high blood sugar level and is caused by an increase in glucose levels due to a progressive decrease in insulin secretion caused by insulin resistance. The ability of diabetic patients to do appropriate and succesful self-care habits is closely related to morbidity and mortality and significantly affect productivity and quality of life. Purpose: The purpose of this study is to determie the correlation between family support and self care agency with quality of life of diabetes mellitus patient type II.Method: This study uses analitycal methods, namely research that explores how and why health phenomena occur with a cross-sectional approach.Result: The results of the Spearman-Rho test that the P-value in te sig (2-tailed) column 0.123 is more than the level of significance ? 0,05 ( 0,000 < 0,05 ) so it can be concluded that H0 is accepted and H1 is rejected.Conclusion: There is no relationship between self care agency and the quality of life of people with type II diabetes mellitus in prolanic patients